STUDY OF CAMELLIA SINENSIS AND BOSWELLIA SERRATA IN RESPECT TO ANTIANGIOGENIC EFFECT - B., Page Amit; S., Kulkarni Kala (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: The process of angiogenesis is finely balanced by Proangiogenic factors and antiangiogenic factors. Any imbalance between these factors may result in a group of diseases with varied morphologic and pathologic changes, called angiogenesis dependent diseases. One has to arrest the growth of unwanted blood vessels like in metastasis of tumour, arthritis, retinopathies, etc. As the angiogenesis is simultaneously controlled by several factors, one needs to target the whole process through a holistic approach i.e. targeting more than one mechanism at a time. Objective of our study was to evaluate antiangiogenic potentials of Camellia sinensis and Boswellia serrata in whole animal models along with their safety individually as well as in combination. Methods: These extracts were evaluated for their antiangiogenic effect using three models – Chicken Chorioallentoic membrane assay, Rat Subcutaneous air sac and Mesenteric window angiogenesis. Results: The results of toxicity study showed that aqueous extracts of Camellia sinensis and Boswellia serrata are safe on oral administration in acute as well as repeated dose toxicity studies. It also showed antiangiogenic effects of individual extracts as well as their combinations. The study suggests that there may be synergistic effect in these extracts particularly in mesenteric window model. Conclusion: From the study it can be concluded that these extracts can be clinically evaluated on angiogenesis dependent diseases.